Impact of hybridization on Lepus timidus and L. Europaeus gut microbiota in the Italian Alps - Marinangeli, L.; Galla, G.; Crestanello, B.; Praeg, N.; Rzehak, T.; Nonnis Marzano, F.; Seeber, J.; Illmer, P.; Hauffe H. C. (2024)
The mountain hare (Lepus timidus) is a boreal mammalian species, with relict populations in the Alps threatened by climate change due to snow cover reduction and by habitat loss. An additional risk factor is hybridization with the European brown hare (L. europaeus), which is shifting its range to higher altitudes, once dominated by the mountain hare. Despite the recorded presence of hybrids between the two hare species in their Alpine ranges, there is a lack of information about the extent, altitudinal distribution and impact of hybridization. Since gut microbiota is known to affect mammalian health, but is also species- specific, depending on diet, physiology and evolutionary history, hybridization between the two hare species could affect microbiota composition and function, and thus species adaptability and survival. Using non-invasive (faecal pellet) samples, we investigated the altitudinal distribution of L. timidus, L. europaeus and their hybrids to evaluate the current extent of overlap of the two species in an LTSER site in the Autonomous Province of Bolzano/Bozen – South Tyrol, Italy. Using a subset of these samples, we then investigated bacterial and fungal microbiota to understand whether its diversity and composition are influenced by species and/or altitude, and how hybrid’s gut microbial communities compare to that of the two species. Fresh faecal pellets were collected in the field in 2019 and 2020 at Val di Mazia/Matschertal, Italy at four different altitudes (1,000, 1,500, 2,000 and 2,500 m). A fragment of the mtDNA (D-loop) and 10 STR loci were used for individual genotyping, and the results were combined to identify species and hybrids. Gut microbiota richness and composition were investigated using amplicon sequencing of the 16S rRNA gene and fungal ITS2 regions and meta-taxonomic bioinformatics. L. timidus was more common at 2,000–2,500 m, but L. europaeus ranged across the study site, with hybrids found between 1,500–2,500 m. Gut microbiota analysis showed that bacterial alpha diversity did ...